The role of archives and archival sources in history teaching in Croatia, exemplified by the teaching of contemporary Croatian history - Barunčić Pletikosić, Julija (Moderna arhivistika, 2024)
Focusing on Croatia's primary and grammar school curricula and the content of history textbooks about contemporary Croatian history, this paper examines the integration of archival sources into history education, as well as the role of archives as heritage institutions in history teaching. The use of historical sources, one of the six main technical concepts in the teaching of history, is prescribed according to the curriculum for History for Primary Schools and Grammar Schools in the Republic of Croatia. Historical sources are analyzed both quantitatively and qualitatively, including visual and written sources. Primary or archival historical sources are singled out and described.
Keywords: archival sources; archives and education; archives and history teaching; arhivi in izobraževanje; arhivi in učenje zgodovine; arhivski viri; Croatia; history textbooks; Hrvaška; zgodovinski učbeniki